Identification and antimicrobial susceptibility profile of bacterial pathogens isolated from wound infections in a tertiary hospital, Bayelsa, South southern, Nigeria - B. Abdu, Abdulrashed; Egbagba, John; G. Fente, Beleudanyo (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Infected wounds in particular, those associated with antimicrobial resistant microorganisms constitute a significant source of physical, psychological, and economic burden to patients in particular, and the society at large in terms of the huge resources spent in treating such wounds as well as time/days lost at workplaces leading to increased morbidity and mortality globally. The present study sought to investigate and identify the common bacteria associated with wound infections and their antibiotic sensitivity pattern. Material and Methods: A total of 130 wound samples were collected by doctors in ward using Sterile Swab Sticks over a period of 6 months from February-July 2019. Pathogenic bacteria were isolated, identified and their antibiotic susceptibility tests were performed. Results: Among 130 cases, 108 (83.08%) were culture positive for bacterial pathogens, while 22 (16.92%) were bacteriologically sterile (Negative). Rate of infection was high in males (56.15%) than females (43.85%). Of the 108- culture positive, 164 isolates were recovered of which 28 (17.07) were anaerobes, while 136 were aerobes of which 106 (64.64%) were Gram-negative species and 30 (18.29%) Gram-negative species. The predominant isolates among the facultative aerobes, were Pseudomonas aeruginosa 28 (17.07%), followed by E. coli 19 (11.58%), Klebsiella pneumonia 17 (10.37%) while the least were amongst Morganella morgani, Providencia rettgeri and Serretia marcescens with 2 (1.22%) individually. Among the Gram-positive, Staphylococcus aureus 10 (6.10%) were most common, followed by Enterococcus spp 4 (2.44%), Coagulase negative staphylococcus (CoNS) 4 (2.44%) while the least were amongst Streptococcus Group B, Streptococcus Group C, Streptococcus Group G with 2 (1.22%) separately. Amongst the anaerobes, Bacterioides fragilis 16 (9.75%) is the most common, followed by Peptostreptococcus spp., and Prevotella spp with 4 (2.44%) each, while Fusobacterium spp and Veillonella spp were the least, 2 (1.22%) each. Amikacin and nitrofurantoin are the most efficacious for managing wound infections, with all the isolates being susceptible to them. Resistance was moderate to Levofloxacin (49.39%). On the other hand, resistance were above average among Ciprofloxacin (96.34%), Cloxacillin (94.51%), Ceftriaxone (91.46%), Ceftazidine (91.46%), Cefotaxime (87.20%), Erythromycin (59.15%), Ofloxacin (58.54%) and Chloramphenicol (51.22%). The least resistance shown to Gentamicin (16.46%), Streptomycin (16.46%), Imipenem (7.93%), Metronidazole (7.93%), and Piperacillin-tazobactam (7.93%). Conclusion: Antibiotic susceptibility test is suggested prior to administration of antibiotics for successful treatment and intermittent monitoring is also encouraged to check emerging multidrug resistant trends as a guide to health authorities.